Analysis on net profit earned by a company to dividend shared to investors (Case study of PT. Gudang Garam from 2014-2019) - Sri Marti Pramudena (STIE Binaniaga, 2020)
Dividend is profits generated by the company distributed to shareholders. Dividend sharing depends not only on company profits but also on the working capital it obtains. Many companies survive and develop, but the distribution of dividends is fixed and not in line with the development of corporate profits. Thus, this study was aimed to determining the effect of the amount of capital and dividends distribution and the effect of company profits on the number of dividends. The indicator is the type of working capital used, company profits and dividends distributed to the company during the observation period. Research results show that there is no effect of working capital on dividends distributed. Keywords: Capital, Company Profit, Dividend Introduction